2022
DOI: 10.1101/2022.10.17.512540
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elasmobranch genome sequencing reveals evolutionary trends of vertebrate karyotype organization

Abstract: Genomic studies of vertebrate chromosome evolution have long been hindered by the scarcity of chromosome-scale DNA sequences of some key taxa. One of those limiting taxa has been the elasmobranchs (sharks and rays), which harbor species often with numerous chromosomes and enlarged genomes. Here, we report the chromosome-scale genome assembly for the zebra sharkStegostoma tigrinum, an endangered species that has the smallest genome sequenced to date among sharks (3.71 Gb), as well as for the whale sharkRhincodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 83 publications
0
3
1
Order By: Relevance
“…In accordance with previous studies (Oulion et al 2010), we identified 34 Hox genes in this dataset (Supplementary Figure 5, Supplementary Table 9). We found no evidence for the HoxC cluster known to be present in the elephant shark Callorhinchus milii (Ravi et al 2009) and the zebra shark Stegostoma tigrinum (Yamaguchi, Uno, et al 2023). Over 24,473 NCBI sequences, 11,945 (48.8%) were extended with a mean addition of about 1,845 bp per prolonged sequence.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…In accordance with previous studies (Oulion et al 2010), we identified 34 Hox genes in this dataset (Supplementary Figure 5, Supplementary Table 9). We found no evidence for the HoxC cluster known to be present in the elephant shark Callorhinchus milii (Ravi et al 2009) and the zebra shark Stegostoma tigrinum (Yamaguchi, Uno, et al 2023). Over 24,473 NCBI sequences, 11,945 (48.8%) were extended with a mean addition of about 1,845 bp per prolonged sequence.…”
Section: Resultscontrasting
confidence: 69%
“…Hox protein sequences from a range of cartilaginous fish (Supplementary Table 3) and humans were downloaded from NCBI, and used as queries in tBLASTn searches of the Scyliorhinus canicula gene model dataset (Mayeur et al 2021) and the genome assembly. We also used chondrichthyan and human protein sequences of the HoxC flanking genes tspan31 , ddx23 , rnd1 , adcy6 , smug1 , and copz1 (Yamaguchi, Uno, et al 2023) to identify the syntenic region in the S. canicula assembly.…”
Section: Methodsmentioning
confidence: 99%
“…Our k-mer-based estimate of its genome size using raw sequence reads resulted in an even smaller value of approximately 1.7 Gbp. Similarly, for the zebra shark Stegostoma tigrinum whose nuclear DNA content was estimated to be 3.70 Gb (C-value =3.79 pg), the total sequence length of the genome assembly released previously by us 30 (sSteFas1.1; GCA_022316705.1) amounts to only 2.771 Gbp. Our k-mer-based estimate of its genome size using raw sequence reads resulted in approximately 2.805 Gbp.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel with the genome size estimate using the flow cytometry and qPCR, those of the zebra shark and thorny skate were estimated in silico based on k-mer frequency distribution with a conventional procedure. For the zebra shark, short-read genomic data produced previously by us 30 (see Yamaguchi et al, 2022) were used. For the thorny skate, short-read genomic data produced by the Vertebrate Genomes Project 31 was downloaded from VGP GenomeArk (s3://genomeark/species/Amblyraja_radiata/sAmbRad1/genomic_data/illumina/).…”
Section: Methodsmentioning
confidence: 99%